Arsenate retention mechanisms on hematite with different morphologies evaluated using AFM, TEM measurements and vibrational spectroscopy. (15th September 2018) - Di Iorio, Erika; Cho, Hyen Goo; Liu, Ying; Cheng, Zhongqi; Angelico, Ruggero; Colombo, Claudio
Abstract: Lenticular, ellipsoidal and flat tubular hematite particles were precipitated from ferric nitrate solutions in presence of minor amounts of Al, Si, Mg and organic acids (oxalic, citric and tartaric). Particle shape identification was performed using Atomic Force Microscopy (AFM) and Transmission Electron Microscopy (TEM). Arsenate adsorption onto hematite with different morphologies was studied in batch experiments and through vibrational spectroscopy. Three bands assigned to As(V)–O–Fe at, respectively, 920, 895 and 820 cm −1 were in agreement with sorption data indicating inner-sphere complexes. As(V) adsorption kinetics was well described by a general model for diffusion into microporous surface sites showing large difference among the studied hematite samples. The maximum As(V) adsorption occurred near pH 4.0 while at alkaline pH there was a significant decrease of adsorption as confirmed by the shift of infrared As–O stretching bands of arsenate group. A change from tetrahedral Td symmetry to more stable symmetric groups such as C3v (monodentate complex), C2v (bidentate binuclear) or C1v (edge-sharing, bidentate binuclear) was deduced for As(V) sorbed on hematite. Fast arsenate adsorption was higher on ellipsoidal hematite particle with a dominant non basal (1 1 0) face. On the contrary, electrostatic attraction interaction could explain the fast As(V) adsorption on platy morphology characterized by basal face (0 0 1). Despite the discrepancy between theoretical considerations and experimental observations, the present contribution could lead to better understanding of the role played by hematite morphology on surface complexation model to describe arsenic adsorption behavior. Diffusional mass transport models applied to As sorption systems can explain such divergence due to: (i) external mass transport across the boundary layer surrounding the particle; (ii) diffusional mass transfer within the internal structure of the adsorbent particle by a nanopore, (iii) heterogeneity of the surface site. These findings are relevant to understanding the rates of interfacial processes involving arsenate sorption that can be take into account in mass transport models used for the removal of arsenic from contaminated water or wastewaters.